How are China's state-owned enterprises doing in the 1990s? Evidence from three interior provinces - Martin Raiser (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
Since its inception in the early 1980s, the success of China's enterprise reforms remains hotly debated. This paper introduces a new element into the analysis of state-owned enterprise performance by drawing on the recent increase in interregional income disparities. It is argued that as a result of less favourable structural conditions and stronger fiscal dependence on the central government, reform implementation in the interior provinces has lagged behind the progress made along the coast. This hypothesis is investigated using enterprise survey data from three interior provinces which is compared to a similar survey carried out earlier in four coastal cities. The evidence generally supports the view of larger administrative restrictions in the interior and relatively poor economic performance.
Keywords: P42; D2; 330; State-Owned Enterprises; Autonomy; Technical Change; China; Öffentliches Unternehmen; Rentabilität; Produktivität; Regionale Disparität; China